Diseases of the abdomen and Pelvis Diagnostic Imaging and Interventional Techniques - Hodler, J.; Schulthess, G.K. von; Zollikofer, C.L (Springer Milan : Imprint: Springer, 2006)
Written by internationally renowned experts, this volume is a collection of chapters dealing with imaging diagnosis and interventional therapies in abdominal and pelvic disease. The different topics are disease-oriented and encompass all the relevant imaging modalities including X-ray technology, nuclear medicine, ultrasound and magnetic resonance, as well as image-guided interventional techniques. The book represents a condensed overview of twenty topics relevant in abdominal and pelvic disease, and is aimed at residents in radiology as well as at experienced radiologists wishing to be updated on the current state-of-the art.